THE COMPETENCE OF THE EDUCATOR IN THE APPLICATION OF TECHNOLOGIES FOR THE ORGANIZATION OF HEALTH CARE WORK FOR CHILDREN OF PRESCHOOL AGE - Esonova Maloxatxon Akilovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article addresses the issues of educator competence in the use of technology in the organization of health care for preschool children.